The imaging of osteomyelitis - Lee, Yu Jin; Sadigh, Sufi; Mankad, Kshitij; Kapse, Nikhil; Rajeswaran, Gajan (Quantitative imaging in medicine and surgery, 2016)
Osteomyelitis is an important cause of morbidity and mortality in children and adults. Imaging plays a crucial role in establishing a timely diagnosis and guiding early management, with the aim of reducing long-term complications. Recognition of the imaging features of osteomyelitis requires a good understanding of its pathogenesis. In this review, the key imaging findings in osteomyelitis are correlated with the underlying pathological processes. There is a particular emphasis on magnetic resonance imaging (MRI), which is the best available imaging modality owing to its high sensitivity for detecting early osteomyelitis, excellent anatomical detail and superior soft tissue resolution. However, other modalities such as nuclear medicine and computed tomography (CT) are also useful in many clinical contexts, and will also be described in this review.